Ways to open innovation: main agents and sources in the Portuguese case - Fernandes, Silvia (2019)
Facing increasing open innovation trends, Portuguese enterprises are considering the related processes and impacts. Thus, this work aims to identify the sectors whose enterprises most engage in open innovation (such as cooperation on this issue) and which sources/agents are most used. This is analyzed by sector and type of innovation as an interesting way of differentiation for better open innovation strategy delineation. Using the data from the Community Innovation Survey (CIS-2012), it first appraises the nature of the innovation process, either cooperative or firm-based, as the starting level of analysis. Then, it differentiates the results by sector illustrating which cooperation sources/agents are most used (scope) and relative intensity of use (scale). This is important to assess levels of openness and related factors. Results show that main innovating sectors in Portugal are of three types: research-based, knowledge-based and service-based. They reveal an increasing focus on knowledge and services, trends that have been leading to more active openness towards innovation. For instance, health and construction are increasing their openness for innovating and internationalizing processes. However, Portuguese innovation is still more firm-based (in-house) than cooperation-based, especially concerning new products' launching. This work and future analyzes around it can contribute to encourage the open innovation strategy in more sectors of the economy as an easy and effective way to cope with rapid trends and changes. (C) 2017 Elsevier Ltd. All rights reserved.